2022
DOI: 10.3389/fcvm.2022.919293
|View full text |Cite
|
Sign up to set email alerts
|

Pregestational diabetes alters cardiac structure and function of neonatal rats through developmental plasticity

Abstract: Pregestational diabetes (PGDM) leads to developmental impairment, especially cardiac dysfunction, in their offspring. The hyperglycemic microenvironment inside the uterus alters the cardiac plasticity characterized by electrical and structural remodeling of the heart. The altered expression of several transcription factors due to hyperglycemia during fetal development might be responsible for molecular defects and phenotypic changes in the heart. The molecular mechanism of the developmental defects in the hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…Transmission of the electrical impulse for coordinated contractions occurs via the cardiac conduction system of the heart. In the study by Alam et al in newborn rats born from diabetic rats, a decrease in the expression of Bmp4 and Pitx2 , two genes associated with the regulation of the cardiac conduction system, was observed 32 . These data may be relevant to our findings of the PR interval showing altered cardiac electrophysiology in neonates born to pregnancies with gestational diabetes.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Transmission of the electrical impulse for coordinated contractions occurs via the cardiac conduction system of the heart. In the study by Alam et al in newborn rats born from diabetic rats, a decrease in the expression of Bmp4 and Pitx2 , two genes associated with the regulation of the cardiac conduction system, was observed 32 . These data may be relevant to our findings of the PR interval showing altered cardiac electrophysiology in neonates born to pregnancies with gestational diabetes.…”
Section: Discussionsupporting
confidence: 73%
“…In the study by Alam et al in newborn rats born from diabetic rats, a decrease in the expression of Bmp4 and Pitx2, two genes associated with the regulation of the cardiac conduction system, was observed. 32 These data may be relevant to our findings of the PR interval showing altered cardiac electrophysiology in neonates born to pregnancies with gestational diabetes. Regarding the fetal cardiac effects of hyperglycemia, Turan et al reported decreased fetal myocardial function in the first trimester of diabetic pregnancies.…”
Section: Discussionmentioning
confidence: 58%
“…In line with this, time course qPCR analysis revealed disparities in the regulation of GATA4 , NKX2-5 , and TBX5 at different time points throughout development, highlighting the importance of fine transcription control during early development. PGDHOs also presented arrhythmias and reduction in beat frequency, a phenotype that has not been described in diabetic embryonic cardiomyopathy but has been observed in neonatal rats from diabetic mothers ( Alam et al., 2022 ).…”
Section: Discussionmentioning
confidence: 86%
“…These phenotypes were consistent with outcomes found in PGD-induced CHD in animal models and human clinical reports 15,55,56,60 . PGDHOs also presented arrythmias and reduction in beat frequency as determined by calcium imaging, a phenotype that has not been described in diabetic embryonic cardiomyopathy but has been observed in neonatal rats from diabetic mothers 61 and diabetic human adults, which typically exhibit reduced calcium pump activity leading to diastolic dysfunction 62 .…”
Section: Discussionmentioning
confidence: 92%